MULTICULTURALISM: Values Implementation in Educational Institution - Retno Triasvi; Slamet; Eko Heri Widiastuti; Nuryanti Nuryanti (PROCEEDING AL GHAZALI International Conference, 2023)
The aim of the research is to describe and analyze: 1) the scope of multicultural education; 2) multicultural education approches in plural countries; and 3) the urgency of multiculturalism-based education in educational institution. Types of research used qualitative with fenomenology approach. The research held in Semarang with the objects some of public and private senior high school/vocational school. The key informan is policy maker in Semarang education authorities, whereas the additional informan is senior high school/vocational school history teachers in Semarang. Data collection technique used observation and interview, whereas data analysis technique used interactive from Miles and Huberman. The result of the research concluded that multiculturalism-based education is education that specifically focuses on understanding and awareness of the diversity of cultural values. Cultural diversity is something that must be considered by curriculum developers and must be able to accommodate cultural differences, use of culture as a source of content and a starting point for cultural development, understanding of other people’s culture, tolerance, awakening a national spirit based on unity in diversity, development of ethical behaviour, and what is no less important is being able to utilize personal culture as part of entry-behaviour.